2022
DOI: 10.1111/caje.12611
|View full text |Cite
|
Sign up to set email alerts
|

Trade creation and trade diversion in deep agreements

Abstract: Preferential trade agreements have boomed in recent years and extended their reach well beyond tariff reduction, to cover policy areas such as investment, services, competition and intellectual property rights. This paper uses new information on the content of preferential trade agreements to examine the trade effects of deep agreements and revisit the classic Vinerian question of trade creation and trade diversion. Our results indicate that deep agreements lead to more trade creation and less trade diversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 53 publications
3
61
0
1
Order By: Relevance
“…Trade creation makes it easier for member countries to sell and buy each other's products to be more efficient than fellow member states that are members. According to Wibowo (2009); Firdaus (2011); and Mattoo et al (2017), trade creation has a good impact on its member states. Firdaus (2011) and Darsono (2015) revealed that the good impact was also received by nonmember countries as a result of the specialization of production and caused an increase in exports to countries the Rest of the World (RoW).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Trade creation makes it easier for member countries to sell and buy each other's products to be more efficient than fellow member states that are members. According to Wibowo (2009); Firdaus (2011); and Mattoo et al (2017), trade creation has a good impact on its member states. Firdaus (2011) and Darsono (2015) revealed that the good impact was also received by nonmember countries as a result of the specialization of production and caused an increase in exports to countries the Rest of the World (RoW).…”
Section: Literature Reviewmentioning
confidence: 99%
“…DTAs present an avenue for promoting trade and GVC integration in Latin America and the Caribbean. Globally, deep provisions in trade agreements contribute to increases in GVC-related trade (Mattoo, Mulabdic, and Ruta 2017;Orefice and Rocha 2012;and Osnago, Rocha, and Ruta 2017). DTAs are also related to the way firms internationalize (inside the firm's national boundary through vertical integration or outside it through arm's-length transactions).…”
Section: Dtas As a Vehicle For Trade And Gvc Integrationmentioning
confidence: 99%
“…10 The database contains detailed information on the commitments included in 18 policy areas across 283 PTAs signed and notified to the WTO between 1958and 2017. 11 SPS and TBT provisions are covered in, respectively, 269 and 263 PTAs signed between 1960and 2017 The templates used for the mapping of these provisions cover areas such as (a) the reference to the WTO rules; (b) the type of integration approach (harmonization versus mutual recognition) for standards, technical regulations, and conformity assessment procedures, (c) transparency; (d) institutions or mechanisms to administer the agreement and solve disputes; and (e) cooperation among regional partners on standards-related issues. 13 A set of essential provisions are identified which comprise substantive provisions, that is, 10 See https://datatopics.worldbank.org/dta/index.html.…”
Section: Deep Trade Agreements Databasementioning
confidence: 99%
“…A first extensive literature studies the impacts of preferential trade agreements on trade using structural gravity equations. Some selected key papers are Baier and Bergstrand (2007); Baier et al (2014); Mattoo et al (2017);Larch et al (2018); Baier et al (2019); Correia et al (2020); Disdier et al (2020); Anderson and Yotov (2020). These papers provide evidence of a strong positive impact of PTAs on bilateral trade based on state-of-the-art estimates of gravity equations by PPML.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation